Electrification of Kathmandu Thundercloud: A Possible Mechanism - Baral, D. R.; Baral, K. N. (Tribhuvan University Journal, 2010)
A Simple model has been developed with the plausible asumptions, and current terms that thundercloud are set up during thunderstorm activities . The electric field is then estimated for various values of RC time constant for field growth after lightning discharges as observed in the recovery curves of electric field recorded at ground level in Kathmandu Valley. Key words: Plausible asumptions; Thundercloud; Ground level ; Kathmandu Valley Tribhuvan University Journal Volume XVI, 1993 Page: 12-18 Uploaded date: 3 October, 2010